Effects of bacterial quorum sensing degrader on Artemia franciscana culture - Lim, Yan Li (2013)
Quorum sensing is a bacterial cell-to-cell communication with small signal molecules such as acyl-homoserine lactones (AHL) that can regulates the virulence of many pathogenic bacteria. Therefore, quorum sensing interference using degrader strains is a biocontrol strategy to fight bacterial infections. In this study, one of the quorum sensing degrader strains, BP-ART/6 was successfully isolated from Artemia franciscana by enriching newly hatched Artemia nauplii in AHL. Anti-quorum sensing activity of BP-ART/6 was screened using Chromobacterium violaceum CV026 biosensor bioassay, and having the best degradation properties which fully degrade 10ppm of AHL in less than 24 hours. The Gram staining test indicated BP-ART/6 as Gram-negative bacteria. Strain BP-ART/6 was resistant to antibiotic kanamycin and rifampicin at 20, 50 and 100ppm, respectively after 24 hours and 48 hours of incubation. Result from antibacterial study showed BP-ART/6 has no antibacterial activity against Vibrio campbellii ATCC14126, Vibrio alginolyticus ATCC17749 and Vibrio anguillarum ATCC43313. Significant differences (p < 0.05) of survivability in the presence of the degrader strain can be observed between control and the treatment with the QS degraders at both 105 and 106 CFU/ml for 6, 12 and 24 hours. At the same time, encapsulation of degrader strains BP-ART/6 by Artemia was less than 30 colonies as the bacterial counts lay below the countable range of 30 to 300 colonies.